A Historic and Current Sketch of Indigenous Education In Hawaii: With Emphasis on Funding - John A. Thompson (Educational Considerations, 1993)
While it is unfair to blame education for all problems, there seems little doubt that the drive to Americanize the schools had an effect on a native culture which varied greatly from a western style.